Yolk−Shell Nano ZnO@Co‐Doped NiO with Efficient Polarization Adsorption and Catalysis Performance for Superior Lithium−Sulfur Batteries. Issue 3 (22nd December 2020) - Xu, Pingdi; Liu, Handing; Zeng, Qingwen; Li, Xiao; Li, Qing; Pei, Ke; Zhang, Yahui; Yu, Xuefeng; Zhang, Jie; Qian, Xiang; Che, Renchao
Abstract: Achieving strong adsorption and catalytic ability toward polar lithium polysulfide species (LiPSs) of the sulfur host in lithium–sulfur (Li–S) batteries is essential for their electrochemical cyclic stability. Herein, a strategy of "self‐termination of ion exchange" is put forward to synthesize the novel yolk‐shell sulfur host composed of ZnO nanoparticles confined in Co‐doped NiO (CDN) polyhedron (ZCCDN). After sulfur infiltration, the obtained S/ZCCDN cathode achieves excellent performance of 738.56 mAh g −1 after 500 cycles at 0.5 C with a very low capacity decay rate of only 0.048% per cycle. Even at 1 C, 501.05 mAh g −1 could be retained after 500 cycles, suggesting a capacity decay ratio of only 0.076% per cycle. The good cycle performance is attributed to the improved LiPSs' conversion kinetics, which originates from ZCCDN's sturdy chemical affinity and strong catalytic ability to polar LiPSs. For the first time, by electron holography, the local interfacial polarization electric field is clarified to be existed in the material which is conducive to the capture of LiPSs and the migration of electrons and Li + from the mesopores. This work provides a rational way for the use of zeolitic imidazolate frameworks (ZIFs) and development of cathode materials for Li–S batteries. Abstract : The novel structure composed of ZnO nanoparticles confined in Co‐doped NiO polyhedron is for the first time synthesized by new strategy of "self‐termination of ion exchange." This material shows outstanding cyclic stability with 738.56 mAh g −1 remained after 500 cycles at 0.5 C and low decay rate of only 0.048% per cycle due to efficient polarization adsorption and catalysis ability.